What drives the demand for high-cost consumption loans? - Emil Toft Hansen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
This paper utilizes high-quality transaction data from the largest bank in Denmark to study what drives the demand for high-cost consumption loans. I investigate the extent to which adverse events drive loan demand, or if it is more likely to be explained by borrowers' personality traits. I find no evidence suggesting that borrowers suffer expenditure, health or social shocks at the time of borrowing. There are indications that some borrowers suffer income shocks, but the magnitude is too modest for this to be an important determinant of aggregate loan demand. Instead, I find evidence pointing towards a dominant role for borrowers' personality traits in explaining loan demand. Using paycheck sensitivity as a proxy, I show that high-cost borrowers appear to be significantly more present-biased than other consumers. I also document that high-cost borrowers are more prone to temptation spending as they spend much more on gambling than other consumers, both leading up to and when borrowing for the first time. Further, I find that high-cost borrowers persistently spend more than they earn and that this gap widens further as they approach the time of their first high-cost loan. Lastly, I document a large increase in non-essential spending around the time of borrowing. Taken together, the results indicate that high-cost borrowers have self-control problems and that high-cost loans are likely used to finance impulse spending or function as a way to prolong a credit-financed spell of overconsumption.
Keywords: D12; D14; D15; D18; G51; 330; High-Cost Credit; Payday Loans; Consumption Loans; Household Finance; Consumer Behaviour; Transaction Data